AI-Powered Simulations for Medical Training: A Game-Changer in Skill Development - Latif Bagwan; Rajesh Gouri; Avani V Mendpara; Azmat Kamal Ansari; Brijesh R. Koyani (Medical Science: Trends and Innovations Vol. 13, 2025)
The integration of Artificial Intelligence (AI)-powered simulations in medical training has revolutionised skill development by providing an interactive, immersive, and adaptive learning environment. These simulations leverage machine learning, virtual reality (VR), augmented reality (AR), and deep learning algorithms to create realistic clinical scenarios, enabling medical professionals to practice decision-making, procedural techniques, and diagnostic skills in a risk-free setting. AI-driven simulations enhance competency-based education, personalised learning, and real-time feedback, ensuring improved clinical proficiency and patient safety. This book chapter explores the role of AI-powered simulations in medical education, their impact on cognitive and psychomotor skill acquisition, and the challenges associated with their adoption. The findings suggest that AI-based simulations are a game-changer in medical training, offering scalable, cost-effective, and high-fidelity learning experiences that bridge the gap between theoretical knowledge and real-world clinical practice.